Cyber-stalking victimization: what predicts fear among portuguese adolescents? - Pereira, Filipa (2016)
A large body of research clearly demonstrates that adolescents use technology to a staggering degree and that they are one of the main groups that are vulnerable to online victimization. However, the study of cyber-stalking, which is a form of cyber-harassment victimization, has been limited to the adult population and has resulted in some controversy regarding whether fear is a definitional criterion for this phenomenon. In Portugal, the study of cyber-stalking among adolescents is limited, as it is not yet a target of scientific research, public politics or social attention. The current study assessed the cyber-stalking victimization of 627 Portuguese adolescents (12- to 16-years-old). The prevalence of victimization, the cyber-victim's profile, cyber-stalking dynamics, the cyber-stalker's profile, parental cyber-involvement and adolescents fear reporting were analysed. The majority of the current sample admitted to having been the victim of cyber-stalking at some point in their life, and nearly half of the adolescents reported experiencing fear after the victimization. A logistic regression model was developed to predict fear reporting. Consistent with previous research, the results indicated that fear is strongly associated with female victims and shed light on the self-perception of online risk and a number of parental involvement practices. Being the target of 1) messages of exaggerated affection, 2) persistent cyber-stalking or 3) older cyber-stalkers was also associated with fear. These results underscore the importance of understanding fear as a complex emotion that results from the interaction of different variables. Thus, it is critical to adopt fear as a key criterion of the cyber-stalking definition. Implications for social, educational, political and judicial practices are also discussed.